'Blinded by Quarry Vision': Nicholas Mangan, Australia, and the History of Extraction in the South Pacific. Issue 3 (3rd May 2020) - Magagnoli, Paolo
Abstract: This article explores the work of contemporary artist Nicholas Mangan, whose film and sculptural practice is concerned with capitalist extraction and colonial exploitation in Australia and the South Pacific. It addresses the amnesiac nature of Australian contemporary art, which tends to distance itself from the country's problematic history of intensive mineral extraction and violent settler colonialism. Framing Mangan's practice within the Australian context, the article analyses two of the artist most relevant projects to date: Nauru—Notes from a Cretaceous World (2009–2010) and Progress in Action (2013). In these films and sculptural installations, I argue, the quarry emerges as a space of colonial violence, but also one of potential creativity. The article concludes with an assessment of Mangan's work in relation to the critical debate on the emergence of New Materialist philosophies in contemporary art. In particular, the article considers Mangan's art in relation to the Marxist-post humanism advanced by McKenzie Wark.